Exposure to Household Painting and Floor Treatments, and Parental Occupational Paint Exposure and Risk of Childhood Brain Tumors: Results from an Australian Case-Control Study - Greenop, K.; Peters, S.; Fritschi, Lin; Glass, D.; Ashton, L.; Bailey, H.; Scott, R.; Daubenton, J.; de Klerk, N.; Armstrong, B.; Milne, Elizabeth (Kluwer Academic Publishers, 2014)
Purpose: Childhood brain tumors (CBT) are the leading cause of cancer death in children, yet their etiology remains largely unknown. This study investigated whether household exposure to paints and floor treatments and parental occupational painting were associated with CBT risk in a population-based case–control study conducted between 2005 and 2010.Methods Cases were identified through all ten Australian pediatric oncology centers, and controls via nationwide random-digit dialing, frequency matched to cases on age, sex, and state of residence. Data were obtained from parents in mailed questionnaires and telephone interviews. Information on domestic painting and floor treatments, and parental occupational exposure to paint, in key periods relating to the index pregnancy and childhood was obtained for 306 cases and 950 controls. Data were analyzed using unconditional logistic regression, adjusting for frequency matching variables and potential confounders. Results: Overall, we found little evidence that parental, fetal, or childhood exposure to home painting or floor treatments was associated with risk of CBT. There was, though, some evidence of a positive association between childhood exposure to indoor painting and risk of high-grade glioma [odds ratio (OR) 3.31, 95 % confidence interval (CI) 1.29, 8.52] based on very small numbers. The OR for the association between CBT and paternal occupational exposure to paint any time before the pregnancy was 1.32 (95 % CI 0.90, 1.92), which is consistent with the results of other studies. Conclusions: Overall, we found little evidence of associations between household exposure to paint and the risk of CBT in any of the time periods investigated.